EVALUASI PELAKSANAAN PROSEDUR TETAP PELAYANAN SURAT KETERANGAN MEDIS DI INSTALASI REKAM MEDIS RSUD KOTA YOGYAKARTA - , ARGA PUSPITA EVI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The medical records service is professional support services oriented to the needs of health information. Function of medical records is important so that the necessary rules (Standard Operating Procedure). In the hospital of Yogyakarta City has not had a complete operating procedures about the services of medical certificate. Incompleteness is not had standard of time and image of service flow. The completeness of the procedure is part of the quality of services and accreditation of hospitals, so it is necessary to evaluate the implementation of procedures. Evaluation results are expected to improve the services of medical certificate. Objective: Evaluate the implementation, process, use, timeliness of the service of medical certificate and make the proposed draft of standard operating procedures in the Installation of Medical Record the hospital of Yogyakarta City. Method: The type of research used in this study was a descriptive study with qualitative approach and use a cross-sectional study design. Subjects were the officers of Administration, the official medical certificate, the medical record officer installation, physicians, and the Chief of Medical Record. Object of study is the implementation of the medical certificate services procedure. Data collection techniques using observation, interviews, and documentation. Results: The place of implementation and the implementer of the medical sertificate services has been implemented in the Installation Medical Record, but there is no space and specialized personnel. Step-by-step implementation of the services are in accordance with existing procedures, but it is not going well and its application is not in accordance with the related manufacturing processes (more than 7 days) so to be given the time constraints and image of service flow. Exposure information of medical record was based patient consent and use valid forms. The medical certificate typed by the officer and signed by a physician in accordance with their authority. Parties that require a medical certificate is the individual (20 requests), insurance (63 requests), the police (8 requests), and institutions (14 requests). The kind of medical certificate is a medical certificate / SKM (20 requests), other insurance claims (36 requests), agency (12 requests), Jasa Raharja (5 requests), Social Security (22 requests), Visum (8 requests), and Mutations (2 requests). The result of recapitulation during January to March 2013 is the medical certificate on time 72.38% and 27.62% late, the highest number of requests Other Insurance Claims (36 requests) and cases of disease internal&general (21 cases), the delay time happen on demand of Jasa Raharja (60%) and Surgical cases (36.36%). The proposed draft of standard operating procedures in this study, the format and content have been referring to the KARS (2001) and has been adapted to the existing theories. Suggestion: Proposed draft of standard operating procedures in this study there is a change, that understanding the patient, heirs, adding purpose and content of the procedure on the manufacturing process, so it can be used as input in the preparation of operating procedures services of a medical certificate.